IDEOLOGI NUBUWWAH DALAM PEMBANGUNAN WILAYAH MELALUI KEBIJAKAN DAN PERSPEKTIF POLITIK IBNU SINA - M Nazri; Abdul Mukti; Zaini Dahlan (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2022)
A politics does not have some rich people who have the power to achieve authority. Understanding Politics will be narrow if it is interpreted as a power conflict to gain position and authority. Politics is the style of humans interacting to form social relations in order to give birth to an equitable and prosperous country, therefore politics belongs together. The state will not be realized as a respectable country if there is no good interaction from the leader and his people. Both of them practice what has been agreed upon together. This article focuses on Ibn Sina's political thought as a social and political analysis found today, especially in Indonesia. Ibn Sina's political ideas lead to nubuwwah as well as foreign political thoughts. Thus, the State Leaders actually practice the values ​​of the Prophetic heritage in their souls. Similarly, what is carried out by the community is to comply with the existing regulations in their territory, so that the realization of a country with noble character is realized.